2015
DOI: 10.1051/0004-6361/201321269
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and thermal structure at the onset of high-mass star formation

Abstract: Context. Even though high-mass stars are crucial for understanding a diversity of processes within our galaxy and beyond, their formation and initial conditions are still poorly constrained. Aims. We want to understand the kinematic and thermal properties of young massive gas clumps prior to and at the earliest evolutionary stages of high-mass star formation. Do we find signatures of gravitational collapse? Do we find temperature gradients in the vicinity or absence of infrared emission sources? Do we find coh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 70 publications
(135 reference statements)
4
26
0
Order By: Relevance
“…A similar VLA survey of IRDC kinematics by Ragan et al (2012) found no values of M below 2, favouring an even higher degree of non-thermal motions present inside the massive dense cores. Three other VLA surveys of ammonia (Lu et al 2014; upper limit of 1.3 km s −1 on line widths in Bihr et al 2015; typical M from 3 to 5 reported in Dirienzo et al 2015) report highly supersonic gas motions within IRDCs. We suggest that the coarser spectral resolution of the previous VLA ammonia studies in similar IRDCs might have inhibited the detection of the subsonic regime, as our spectral resolution of 0.2 km s −1 is higher than that of the previous studies (0.6 km s −1 in Ragan et al 2012;Lu et al 2014;Dirienzo et al 2015; 0.6 km s −1 for most of the data used by Sánchez-Monge et al 2013; 0.8 km s −1 in Bihr et al 2015).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A similar VLA survey of IRDC kinematics by Ragan et al (2012) found no values of M below 2, favouring an even higher degree of non-thermal motions present inside the massive dense cores. Three other VLA surveys of ammonia (Lu et al 2014; upper limit of 1.3 km s −1 on line widths in Bihr et al 2015; typical M from 3 to 5 reported in Dirienzo et al 2015) report highly supersonic gas motions within IRDCs. We suggest that the coarser spectral resolution of the previous VLA ammonia studies in similar IRDCs might have inhibited the detection of the subsonic regime, as our spectral resolution of 0.2 km s −1 is higher than that of the previous studies (0.6 km s −1 in Ragan et al 2012;Lu et al 2014;Dirienzo et al 2015; 0.6 km s −1 for most of the data used by Sánchez-Monge et al 2013; 0.8 km s −1 in Bihr et al 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Three other VLA surveys of ammonia (Lu et al 2014; upper limit of 1.3 km s −1 on line widths in Bihr et al 2015; typical M from 3 to 5 reported in Dirienzo et al 2015) report highly supersonic gas motions within IRDCs. We suggest that the coarser spectral resolution of the previous VLA ammonia studies in similar IRDCs might have inhibited the detection of the subsonic regime, as our spectral resolution of 0.2 km s −1 is higher than that of the previous studies (0.6 km s −1 in Ragan et al 2012;Lu et al 2014;Dirienzo et al 2015; 0.6 km s −1 for most of the data used by Sánchez-Monge et al 2013; 0.8 km s −1 in Bihr et al 2015). Our results thus point to consistently lower line widths and temperatures than those found in other IRDCs, and closer to the typical values in nearby Gould Belt low-mass star-forming regions (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Although the clouds are constantly being deformed by SN explosions, these do not drive substantial internal turbulence. While SN continue to explode in the diffuse ISM, the clouds maintain low velocity dispersions, which appears (Gibson et al 2009); and (yellow stars) infrared dark clouds observed with NH 3 (Bihr et al 2015). The black triangle shows the constant value of the column density reported by Solomon et al (1987) in their size-density relation.…”
Section: Discussionmentioning
confidence: 94%
“…Since a 2-D Gaussian is not suitable for modeling a filamentary structure, we use the same algorithm that measures the total flux per unit projection size to measure the linear masses in rectangles, which are centered on the mapping center of 30 m observations and individually have lengths that are one, two, or three times the local FWHM width, and then derive the mean.17 Even if the velocity distribution of our source is biased by our field of view, rotation energy is in general not comparable to the gravitational energy(Goodman et al 1993;Bihr et al 2015).…”
mentioning
confidence: 99%